ANALISIS PROSES PEMBELAJARAN BERBASIS STUDENT CENTERED LEARNING DALAM PENDEKATAN SAINTIFIK PADA MATA PELAJARAN SEJARAH DI SMA NEGERI SE KOTA PALU - Prasetyawati, Priyatna (Katalogis, 2016)
This research aims at describing (1) the lesson plan on student centered learning based and scientific approach of History subject at all state high school in Palu, (2) the implementation of students centered learning based on scientific approach of History subject, (3) the obstaclesÂ  experienced by teachers in applying the students centered learning based and scientific approach of history subject. The research design used is qualitative approach. The data were collected through literature study and field study such as: observation, interview, and documentation. The data were analyzed through data reduction, data presentation, and data verification. The result of this research showed that the systematic and the component of lesson plan arranged by teacher of History subject at all state high school in Palu is accordance to 2013 curriculum. The students centered learning of History subject has been implemented to all studentsâ€™ at all state high school in Palu through scientific approach and through stages of activities such: observing, asking, collecting information, associating, and communicating. The evaluation given by teachers covered assessment of attitudes, knowledge, skills. Obstacles experienced during the learning process were the revision of 2013 curriculum of history textbooks that have not been distributed yet in the school; half of content of the history textbook published by the government is not in accordance to syllabus, and some facilities at school have not been adequate, the LCD projector and internet connection is limited.